Novel replicative properties of a capsid mutant of bacteriophage phi chi 174. - Vito, C C (1976)
A capsid mutant of bacteriophage phi chi 174 demonstrates altered requirements for the conversion of viral single-stranded DNA to double-stranded replicative form DNA. In the presence of puromycin at 42 C, wild-type phi chi 174 is unable to complete this replicative event, whereas phi chi ahb is able to do so. Furthermore, in contrast to wild-type phi chi 174, formation of phi chi ahb parental replicative form DNA is sensitive to rifampin under certain experimental conditions. These data suggest that the mutant capsid proteins of phi chi ahb influence the biosynthesis of phi chi ahb complementary strand DNA.